Somewhere everywhere nowhere : collections sans Frontières III : contemporary art from the collections of the Frac du Grand Est - Bradley, Fiona; Brown, Katrina M.; Dundee Contemporary Arts, Dundee; The Fruitmarket Gallery, Edinburgh (Dundee Edinburgh : Dundee Contemporary Arts Dundee The Fruitmarket Gallery Edinburgh, 2004)
Alighiero e Boetti ; B.P. ; Baumgarten, Lothar ; Bazile, Bernard ; Becher, Bernd & Hilla ; Bernstrup, Tobias ; Boyce, Martin ; Brotherus, Elina ; Chen Zhen ; Dahlberg, Jonas ; Deleu, Luc ; Doherty, Willie ; Fraser, Andrea ; Garfield, Peter ; Gonzalez-Foerster, Dominique ; Gordon, Douglas ; Grauerholz, Angela ; Huyghe, Pierre ; Limone, Guy ; Marcel, Didier ; Milroy, Lisa ; Morris, Sarah ; Nefzger, Jürgen ; Nicolas, Lalie ; Pouvreau, Paul ; Reip, Hugues ; Struth, Thomas ; Sugimoto Hiroshi ; Wall, Jeff ; Wurm, Erwin
Produced to accompany the exhibition 'Somewhere everywhere nowhere : collections sans Frontières III at the Dundee Contemporary Arts in Dundee, 16.10.2004-04.12.2004 and at The Fruitmarket Gallery in Edinburgh, 16.10.2004-28.11.2004
boek